Erythrocyte oxidative stress markers in children with sickle cell disease - Priscila Bacarin Hermann; Mara Albonei Dudeque Pianovski; Railson Henneberg; Aguinaldo José Nascimento; Maria Suely Soares Leonart (Elsevier, 2016)
Abstract Objective To determine eight parameters of oxidative stress markers in erythrocytes from children with sickle cell disease and compare with the same parameters in erythrocytes from healthy children, since oxidative stress plays an important role in the pathophysiology of sickle cell disease and because this disease is a serious public health problem in many countries. Methods Blood samples were obtained from 45 children with sickle cell disease (21 males and 24 females with a mean age of 9 years; range: 3-13 years) and 280 blood samples were obtained from children without hemoglobinopathies (137 males and 143 females with a mean age of 10 years; range: 8-11 years), as a control group. All blood samples were analyzed for methemoglobin, reduced glutathione, thiobarbituric acid reactive substances, percentage of hemolysis, reactive oxygen species, and activity of the enzymes glucose 6-phosphate dehydrogenase, superoxide dismutase, and catalase. Data were analyzed using Student's t-test and were expressed as the mean ± standard deviation. A p-value of <0.05 was considered significant. Results Significant differences were observed between children with sickle cell disease and the control group for the parameters methemoglobin, thiobarbituric acid reactive substances, hemolysis, glucose 6-phosphate dehydrogenase activity, and reactive oxygen species, with higher levels in the patients than in the controls. Conclusions Oxidative stress parameters in children's erythrocytes were determined using simple laboratory methods with small volumes of blood; these biomarkers can be useful to evaluate disease progression and outcomes in patients.